The Regulatory Effects of mTOR Complexes in the Differentiation and Function of CD4+ T Cell Subsets - Peng Wang; Qian Zhang; Liang Tan; Yanan Xu; Xubiao Xie; Yong Zhao (Journal of Immunology Research)
T cells are an important part of the adaptive immune system and play critical roles in the elimination of various pathogens. T cells could differentiate into distinct cellular subsets under different extracellular signals and then play different roles in maintaining host homeostasis and defense. The mechanistic target of rapamycin (mTOR) is a conserved intracellular serine/threonine kinase which belongs to the phosphoinositide 3-kinase- (PI3K-) related kinase family. The mTOR signaling pathway is closely involved in a variety of cell biological processes, including cell growth and cell metabolism, by senses and integrates various environmental cues. Recent studies showed that mTOR including mTORC1 and mTORC2 is closely involved in the development of T cell subpopulations such as Th1, Th2, Th9, Th17, follicular helper T cells (Tfh), and Treg cells through distinctive pathways. We herein mainly focused on the recent progress in understanding the roles of mTOR in regulating the development and differentiation of CD4+ T cell subsets.